Issue Information. Issue 7 (30th July 2021) - Unknown
Abstract : Cover : Cultured neonatal primary cardiomyocytes from rat and mouse represent an immensely useful model system to study various cellular and sub‐cellular aspects of cardiomyocyte physiology. In this issue, Ravi et al describe a simplified workflow to isolate, culture, and maintain neonatal primary cardiomyocytes from rats and mice. The cover image shows neonatal rat cardiomyocytes cultured on gelatin coated dishes, immunostained for myomesin (green) and labelled with Hoechst (blue), highlighting the M‐line of the sarcomeres. Image provided by Dr. N. Ravi Sundaresan.